Male breast cancer: a case series and review of literature - Choudhary, M. Amir; Syed, Ameenuddin Ali; Syed, Obaid (International Journal of Research in Medical Sciences, 2024)
Male breast cancer (MBC) is a rare condition, representing about 0.5-1% of all breast cancer cases, while recent trends indicate a gradual increase in incidence. This study seeks to examine the clinical and pathological features of MBC patients. This study also sheds light on demographics factors and family history association with the disease. It also identifies various risk factors associated with disease and reviews its surgical management. We conducted a retrospective analysis of six MBC patients treated at the department of general surgery at Indian institute of medical science and research (IIMSR), Jalna, from May 2022 to September 2024. Data were collected on demographics, clinical history, local examination findings, family history, disease stage, histopathological findings and immunohistochemistry (IHC). The findings revealed a median age of 51.5 years at diagnosis. Four patients presented with right breast involvement, while two had left breast involvement. Diagnosis was confirmed with ultrasound (USG) and fine needle aspiration cytology. Four patients had skin involvement while five had clinically palpable axillary lymphadenopathy. Modified radical mastectomy (MRM) was the surgical procedure done in all six cases. Our study also emphasizes early diagnosis to improve outcomes by educational efforts focusing on promoting self-examinations and screening for high-risk populations.